Can we shift and/or broaden the catalysis regime towards ambient temperature? - Gopinath, Chinnakonda S.; Roy, Kanak; Nagarajan, Sankaranarayanan (ChemCatChem, 2015)
An attempt was made to shift the temperature regime of oxidation catalysis towards ambient temperatures by employing surface modification (SM) as a handle. Systematic SM of Pd(111) was performed by O-atom diffusion into the subsurfaces. Virgin and modified Pd(111) catalysts were evaluated for CO oxidation. Typical CO poisoning observed on virgin surfaces was partially lifted, and ambient CO oxidation was observed on the modified surfaces. CO oxidation was followed by the molecular beam method and near-ambient pressure (NAP) photoelectron spectroscopy under different pressure regimes. UV valence band spectral analysis of the SM and the CO+O-2 reaction on modified Pd(111) surfaces under NAP conditions demonstrated changes in the electronic structures of the surfaces with a change in surface potential by 0.35eV and directly probed CO2 formation under the reaction conditions. Supported metal catalysts may be subjected to SM and evaluated for a shift in the catalysis regime for many different reactions.
Keywords: heterogeneous catalysis; Oxidation; photoelectron spectroscopy; surface chemistry; surface modification